The interface between depression and alzheimer's disease. A comprehensive approach - Pedro J Modrego; Leyre D de Cerio; Antonio Lobo (Annals of Indian Academy of Neurology, 2023)
Depression and Alzheimer's disease (AD) are frequent interacting diseases in the elderly with a negative impact on the quality of life of patients and caregivers. Late-life depression may be regarded either as an early symptom of AD or a risk factor for AD, depending on the context. This review was focused on the latest developments in the fields of the neurobiological basis and treatment of depression in AD. We found that some plausible hypotheses are emerging to correlate with depression in AD, such as neuroinflammation and dysimmune regulation. It seems that depression is not related to amyloid deposition, but this issue is not completely resolved. The response to antidepressants is controversial according to the evidence from 10 small double-blind randomized placebo-controlled clinical trials with antidepressants in AD patients with depression: four with sertraline, one with three arms (sertraline, mirtazapine, placebo), one with fluoxetine, one with imipramine, one with clomipramine, one with escitalopram, and one with vortioxetine. The total number of treated patients completing the trials was 638. The main criterion of a positive response was a reduction in the scores of clinical scales for depression of at least 50%. The weighted OR (odds ratio) was calculated with the method of Mantel-Haenszel: 1.29; 95% CI: 0.77–2.16. No significant differences were found compared with placebo. Antidepressants did not have a meaningful negative influence on cognition, which was measured with the mini-mental state examination (MMSE) in 18 clinical trials. Alternatives other than drugs are also discussed. Although there have been important advances in this field, pathophysiology and treatment deserve further research.